ANALISIS PENGARUH BUDAYA ORGANISASI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA APARAT PENGAWAS INTERN PEMERINTAH DAERAH PROVINSI SULAWESI UTARA - Maradesa, Christony; Budiarso, Novi S. (ACCOUNTABILITY, 2017)
This study aims to analyze the influence of organizational culture, leadership style to the performance of APIP. Data were obtained through questionnaires in North Sulawesi Province Inspectorate. Questionnaires were distributed to 39 respondents and were processed with multiple linear regression analysis method using SPSS version 24. The study consists of the dependent variable and independent variables. The dependent variable is the APIP performance, while the independent variables is organizational culture and leadership style. The result is Organizational Culture and Leadership Styles either simultaneously or partially affects the Performance of APIP.Keywords: Organizational Culture, Leadership Style, Performance of APIP